Getting around 'offensive' language - Mohamed Ali, Haja Mohideen (2009)
In the English there are many expressions which may be considered 'offensive' by both native and non-native speakers because they refer to sexual activity, private parts of the body and human waste, in a very crude and unpleasant manner. They are insulting to fellow human beings, besides being distasteful in other ways. Users may therefore find it repugnant to use such expressions in their discourse. The contemporary English language dictionaries which have included them often describe them as offensive, deeply offensive and sometimes even carry a warning not to use them. In order not to give the impression that a speaker is rude, insensitive, vulgar or uncultured, which other alternative words can speakers use? It is especially important for people who live in a society or community which values politeness in language use to be aware of 'bad' language and know how to use words which may be considered free from language unpleasantness. This awareness is not only necessary for non-native speakers of English, but also for those to whom English is their dominant language of communication.